ON THE NUMERICAL SOLUTIONOF VOLTERRA INTEGRAL EQUATIONS - MADJIDI, Imane (Faculty of Mathematics and computer sciences Department of Mathematics - Option : Mathematical and numerical analysis, 2020)
The goal of this memory is consecrated to the numerical solutions of the Volterra integral equations of the first kind by employing the method of collocation based on the polynomial of TChebyshev, thus the method of the trapezoid, by making comparisons.
Keywords: First kind integral equations of Volterra, the collocation method, the polynomial of TChebyshev, numerical quadrature .